2006
DOI: 10.1097/mrr.0b013e328010b961
|View full text |Cite
|
Sign up to set email alerts
|

Reflex sympathetic dystrophy in hemiplegia

Abstract: There is a high incidence of reflex sympathetic dystrophy of the upper limbs in patients with hemiplegia, and its painful and functional consequences present a problem to specialists in physical medicine and rehabilitation. This study was designed to assess the role of several factors in the occurrence of reflex sympathetic dystrophy in patients with hemiplegia. Ninety-five consecutive stroke patients (63 male and 32 female, mean age 59+/-12 years) admitted to our hospital were evaluated. Of the study group, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 13 publications
0
38
1
2
Order By: Relevance
“…In the literature, results of studies assessing the correlation between shoulder subluxation and CRPS-I also show differences (Braus et al, 1994;Davis et al, 1997;Dursun et al, 2000;Daviet et al, 2002) Nonetheless, we found that motor deficit, as shown by lower Brunnstrom recovery stages, was a significant contributing factor in the occurrence of CRPS-I. Similarly, Gokkaya et al (2006) reported that the presence of flaccidity and lower recovery stages were significant factors in the development of CRPS-I.…”
Section: Discussioncontrasting
confidence: 34%
“…In the literature, results of studies assessing the correlation between shoulder subluxation and CRPS-I also show differences (Braus et al, 1994;Davis et al, 1997;Dursun et al, 2000;Daviet et al, 2002) Nonetheless, we found that motor deficit, as shown by lower Brunnstrom recovery stages, was a significant contributing factor in the occurrence of CRPS-I. Similarly, Gokkaya et al (2006) reported that the presence of flaccidity and lower recovery stages were significant factors in the development of CRPS-I.…”
Section: Discussioncontrasting
confidence: 34%
“…This is supported by findings that subluxation is more common in these patients [94] and that the degree of weakness and immobility in the shoulder is related to the probability of developing CRPS [95]. It is postulated that trauma to the affected shoulder is associated with the development of CRPS [96]; however, how this translates into the constellation of symptoms associated with this particular pain syndrome is not known.…”
Section: Common Post-stroke Pain Subtypesmentioning
confidence: 54%
“…The exact mechanism of CRPS after stroke remains unclear [11]. Some investigators have reported that CRPS in hemiplegia was correlated with glenohumeral subluxation [13], while others have reported such correlation to be absent [22]. In the acute stage of CRPS after stroke, one of the possible mechanisms is localized neurogenic inflammation which can explain the clinical symptoms such as local edema, vasodilatation and hyperhidrosis [2].…”
Section: Discussionmentioning
confidence: 98%
“…CRPS in the hemiplegic limb after stroke is common in a rehabilitation setting, with a recently reported incidence of over 30% [13,14]. Early detection and treatment is very important to achieve pain control and functional restoration of the hemiplegic upper limb in a rehabilitation setting.…”
Section: Discussionmentioning
confidence: 99%